Prostaglandin pathways in equine myometrium regulations: endometrosis progression - Piotrowska-Tomala, Katarzyna K.; Szóstek-Mioduchowska, Anna Z.; Drzewiecka, Ewa M.; Jonczyk, Agnieszka W.; Wójtowicz, Anna; Wrobel, Michał H.; Ferreira-Dias, Graca; Skarzynski, Dariusz J. (Frontiers in Veterinary Science, 2024)
IntroductionProstaglandins (PG) are important regulators of the myometrial contractility in mammals. Endometrosis, a condition characterized by morphological changes in the equine endometrium, also affects endometrial secretory function. However, it remains unclear whether and how endometrosis affects myometrial function.MethodsThis study investigated: (i) mRNA transcription of genes encoding specific enzymes responsible for PG synthesis, such as prostaglandin—endoperoxide synthase (PTGS2), PGE2 synthase (PTGES), PGF2α synthase (PTGFS) and PG receptors: PGE2 receptors (PTGER1- 4), and PGF2α receptor (PTGFS) in equine myometrium and, (ii) the effects of PGE2 and PGF2α on myometrial contractile activity, during endometrosis in mares. The myometria used in experiments 1 and 2 were collected from mares in the mid-luteal (n = 23) and follicular (n = 20) phases of the estrous cycle, according to the histological classification of the endometrium (Kenney and Doig categories I, IIA, IIB, and III).ResultsIn experiment 1, changes in mRNA transcription of PG synthase or PG receptors in the myometrium during the course of endometrosis were determined using qPCR. During the mid-luteal phase, myometrial mRNA transcription of PTGES increased in mares with endometrial category IIB compared to category I. However, myometrial mRNA transcription of PTGER1 decreased during the progression of endometrosis compared to category I. During the follicular phase, mRNA transcription of PTGER1 and PTGER2 increased in mares with endometrial categories III or IIA, respectively. In addition, mRNA transcription of PTGFS increased in mares with endometrium category IIA compared to category I. In experiment 2, the force of myometrial contractions was measured using an isometric concentration transducer. In the follicular phase, PGE2 decreased the force of contractions in mares with endometrial categories IIA, IIB, and III compared to the respective control groups. Prostaglandin F2α increased the force of myometrial contractions in mares with category IIA endometrium, whereas it decreased in category IIB compared to the respective control groups.DiscussionWe concluded that in the progression of endometrosis there are changes in the myometrial transcription of mRNA encoding PG synthases and receptors, particularly PTGER1 and PTGER2. Mares with endometrosis had abnormal myometrial contractile responses to PG. These findings suggest that myometrial function may be compromised during the progression of endometrosis.